Analisis Bakteri Methicillin Resistant Staphylococcus aureus (MRSA) pada Pus Infeksi Nosokomial Pasien Pasca Operasi - Rina Idawati; Suliati Suliati; Lully Hanni Endarini; Pestariati Pestariati (JOURNAL SAINS STUDENT RESEARCH, 2025)
Nosocomial infections are a serious concern in healthcare services, particularly among postoperative patients. One of the main pathogens responsible for nosocomial infections is Staphylococcus aureus, especially strains resistant to the antibiotic methicillin (MRSA). MRSA infections can worsen patient conditions, prolong hospital stays, and increase medical costs.This study aims to analyze the presence of MRSA bacteria in pus samples from nosocomial infections in postoperative patients and to determine its prevalence at General Hospital.This research employed a descriptive-analytic observational method using both primary and secondary data from postoperative patients with nosocomial infections. Pus samples were cultured and identified through Gram staining, catalase test, coagulase test, biochemical tests, and antibiotic susceptibility testing using the Microbiology Analyzer TDR-300B Mindray. The study was conducted from August to November 2024.From 41 pus samples collected from postoperative patients with nosocomial infections, 6 samples tested positive for MRSA, indicating a prevalence of 14.6%. Antibiotic susceptibility tests showed resistance patterns to several beta-lactam antibiotic classes.